The Oral Production Of Plosives Produced By Bilingual Speakers (Hunsrückisch-Portuguese) In The Reading Of Portuguese - Gewehr-Borella, Sabrina (2015)
The current study analyzes the phonetic-phonological transfers from Hunsrückisch into Portuguese, related to the sonority of the plosives. To this end, readings of the 'Parable of the Prodigal Son', written in Portuguese and collected from the Alma-H Project (Contatual-Linguistic Atlas of German Minorities in the ‘Bacia do Prata’- Hunsrückisch), are analyzed. The data produced by informants of six research places, are divided into two social groups (low class and high class) and two different ages (generation I and II). The goals of this study are: a) investigate the numbers of transfers in each one of the plosives; b) compare the interlinguistic transfers found with the Hunsrückisch voicing rules, described by Altenhofen (1996), and related to the tonicity of the syllables, and finally, c) check how the different dimensions (diatopic, diastratic, diagenerational), suggested by the theoretical model of pluridimensional dialectology (THUN, 1998, 2010), act in the variety of sonority found into the data analyzed. The results shown allowed us to understand the interlinguistic transfers processes between Hunsrückisch and Portuguese, which contribute to the description of the variety of Portuguese spoken in the regions researched to this study